Naucno-metodiceskie podchody k sozdaniju nacional'noj koncepcii antidopingogo kontrolja v Rossii - Balachnicev, V. V.; Portugalov, S. N. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The purpose of this paper was to describe the world system of the doping control in sports. The authors highlight the basic stages in the history of the development of the doping control in sports. The situation with this kind of control in Russia in comparison with countries of Europe and America is considered. The authors offer new approach to the creation of the doping conception in Russia. They show short-term and long-term purposes and tasks of this conception also.